Etiologies and resistance profiles of bacterial community-acquired pneumonia in Cambodian and neighboring countries' health care settings: a systematic review (1995 to 2012). - Sophie Goyet; Erika Vlieghe; Varun Kumar; Steven Newell; Catrin E Moore; Rachel Bousfield; Heng C Leang; Sokheng Chuop; Phe Thong; Blandine Rammaert; Sopheak Hem; Johan van Griensven; et al. (PLoS ONE)
Objectives Community-acquired pneumonia (CAP) is one of the most important causes of morbidity and mortality worldwide. Etiological data for Cambodia is scarce. We aimed to describe the main etiological agents causing CAP, and their resistance patterns in Cambodia and the greater Mekong region. Methods A review of bacterial etiologies of CAP and antimicrobial resistance in Cambodia and neighboring countries was conducted via: (1) a systematic review of published literature in all NCBI databases using Pubmed, Google scholar, EMBASE, the World Health Organization and the Cambodian Ministry of Health libraries; (2) a review of unpublished data from Cambodia provided by national and international stakeholders working at different tiers of the healthcare system. Results Twenty three articles and five data sources reported etiologies for 5919 CAP patients diagnosed between May 1995 and December 2012, including 1421 (24.0%), 3571 (60.3%) and 927 (15.7%) from Cambodia, Thailand and Vietnam, respectively. Streptococcus pneumoniae and Haemophilus influenzae were the most common pathogens ranking among the five most prevalent in 12 and 10 studies, respectively. Gram-negative bacteria such as Burkholderia pseudomallei and Klebsiella pneumoniae were also frequently diagnosed, particularly in bacteremic CAP in Thai adults and Cambodian children. In Thailand and Vietnam, Mycoplasma pneumoniae and Chlamydia pneumoniae were frequently identified in settings using indirect laboratory testing. Conclusions Based on this analysis, CAP data in Cambodia seems to present etiological and resistance profiles comparable to those of neighboring countries. Findings have been shared with the national authorities upon the revision of the national therapeutic guidelines and were disseminated using a specially created website.